Adaptación psicométrica de la Escala de Acción Planificada de Dedicación al estudio: de la versión retrospectiva a la prospectiva - Chávez-Ventura, Gina; Santa-Cruz-Espinoza, Henry; Grimaldo-Muchotrigo, Mirian; Araujo-Robles, Elizabeth Dany; Dominguez-Lara, Sergio (Instituto de Investigaciones Psicológicas, 2023)
Since few measuring instruments were found on the management of their own learning in university students, the objective was to adapt the Planned Action Scale of Dedication to Study (EAPDE, for its initials in Spanish), from a retrospective to a prospective version; i.e., that the items be written to evaluate the determination to study in the short term. A total of 279 psychology students from two universities in Trujillo and one in Lima (Peru), selected by non-probabilistic sampling. The confirmatory factor analysis was performed with the WLSMV estimation method using Mplus version 7 software. As for the results, the four-factor model has an acceptable fit (CFI = .957, RMSEA = .057 [CI90% .048, .066], WRMR = 1.050) as well as adequate reliability indicators (ω > .70). It was concluded that the EAPDE has adequate evidence of validity regarding its internal structure and reliability; however, further research is required.